2009
DOI: 10.1016/j.cub.2009.02.040
|View full text |Cite
|
Sign up to set email alerts
|

A Hypervariable Invertebrate Allodeterminant

Abstract: Summary Colonial marine invertebrates, such as sponges, corals, bryozoans, and ascidians, often live in densely-populated communities where they encounter other members of their species as they grow over their substratum. Such encounters typically lead to a natural histocompatibility response in which colonies either fuse to become a single, chimeric colony or reject and aggressively compete for space. These allorecognition phenomena mediate intraspecific competition [1–3], support allotypic diversity [4], con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
146
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(152 citation statements)
references
References 37 publications
5
146
0
1
Order By: Relevance
“…Specific allorecognition systems that predate the emergence of lymphocytes and the MHC have been identified in colonial marine invertebrates (26,47). These systems prevent fusion between genetically disparate members of the same species and thus, serve as safeguards against stem cell and germline parasitism (25,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific allorecognition systems that predate the emergence of lymphocytes and the MHC have been identified in colonial marine invertebrates (26,47). These systems prevent fusion between genetically disparate members of the same species and thus, serve as safeguards against stem cell and germline parasitism (25,28).…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquity of rejection responses, particularly among colonial marine invertebrates, has led to the proposal that allorecognition evolved before the emergence of vertebrate adaptive immune systems, characterized by polymorphic MHC molecules and re-arranging lymphocyte receptors, and that it serves to protect the organism against stem cell parasitism (22)(23)(24)(25). The recent identification of specific allorecognition systems in two colonial marine organisms, Botryllus and Hydractinia (26,27), and the characterization of their role in preventing stem cell chimerism (28,29), have confirmed these earlier suspicions. To investigate whether the mammalian immune system mounts an alloimmune response independent of lymphocytes, we studied the cutaneous reaction of RAG Ϫ/Ϫ mice to cells transplanted from allogeneic donors.…”
mentioning
confidence: 99%
“…3 D-1). Fusion can also occur between allogeneic tissues resulting in a common chimeric colony, mostly restricted to close kin (Hauenschild, 1954(Hauenschild, , 1956, which share at least one alr locus (Nicotra et al, 2009;Rosa et al, 2010;Rosengarten et al, 2011;Rosengarten and Nicotra, 2011).…”
Section: Stem Cell Biology In Hydractinia 529mentioning
confidence: 99%
“…Although first pioneering genetic analyses date back several decades (Hauenschild, 1954(Hauenschild, , 1956 in H. echinata) only extensive positional cloning of two allorecognition loci alr1 and alr2 in H. symbiolongicarpus (Mokady and Buss 1996;Cadavid et al, 2004;Schwarz et al, 2007;Nicotra et al, 2009;Rosa et al, 2010;Rosengarten et al, 2011;Rosengarten and Nicotra, 2011) eventually provided evidence for the involvement of molecules belonging to the immunoglobulin superfamily. In 2009 a first gene was identified that encodes a putative transmembrane receptor expressed in all tissues capable of allorecognition.…”
Section: Regulators Of Allorecognition In Hydractiniamentioning
confidence: 99%
See 1 more Smart Citation